Carbon Accounting: Evidence from Carbon Emission Measurement, Recognition, Recording, and Disclosure of Indonesian Energy Companies - Rosa Fitriana; Nayna Rafa Sofiah; Andry Arifian Rachman (AIBPM Publisher, 2026)
The global climate crisis compels energy firms to enhance their environmental transparency through formalized carbon management systems. This study investigates the effects of carbon emission measurement, recognition, recording, and disclosure on corporate carbon accounting implementation. This quantitative verificative study utilizes secondary panel data from listed energy corporations on the Indonesia Stock Exchange (IDX). Data were collected from 96 firm-year observations during 2021–2023 and analyzed via logistic regression. Descriptive statistics show that 86.46% of firms measure emissions, 41.70% recognize emissions, 47.90% record carbon data, and 51% implement carbon accounting. Logistic regression indicates that carbon emission recognition (b = 2.415, p 0.001), recording (b = 1.843, p = 0.002), and disclosure (b = 3.106, p = 0.014) significantly influence implementation. Conversely, carbon emission measurement has no significant effect (b = 0.812, p = 0.192), showing technical calculations remain isolated from formal accounting. Practically, regulators must standardize carbon accounting guidelines, and managers should explicitly integrate emission data into formal reporting to enhance corporate transparency.